Monoclonal antibodies reacting with gliadin as tools for assessing antigenic structure responsible for exacerbation of celiac disease - Stoyanov, S; Tlaskalová, Helena; Kocna, Petr; Krištofová, H; Fric, P; Hekkens, W. T (Immunology letters, 1988)
Monoclonal antibodies reactive with gliadin were prepared by fusion of spleen cells isolated from gliadin-immunized BALB/c mice with myeloma cells. The reactivity of mAbs with different preparations of gliadin and their enzymatic digest were measured using ELISA method. The mAb produced by GL 1 clone was shown to react preferentially with alpha-gliadin and its enzymatic digest.
Keywords: rostlinné proteiny; Antibody Specificity; Celiac Disease; Plant Proteins; Antibodies, Monoclonal; monoklonální protilátky; lidé; specificita protilátek; Antigens; antigeny; protilátky; Antibodies; gliadin; celiakie; Gliadin; Humans